Kualitas Laporan Keuangan Pemerintah Daerah: Studi OPD Kota Semarang - Yuneve Nilamsari; Fatmasari Sukesti; Alwiyah Alwiyah; Ayu Noviani Hanum; R. Ery Wibowo Agung Santoso (MAKSIMUM, 2020)
The study aimed to determine the effect internal control system, human resource competency, utilization of information technology and application of the regional financial accounting system on the Quality of local Government Financial Report (LKPD) in OPD Semarang City. The populasi in this study is OPD office in Semarang City.  While the resource sample was 64 respondents. this study uses a questionnaire which uses a likert scale of 1-5. The data uses in this study are primary data collected through direct questionaires. Data analysis using multiple regression analysis. The result of analysis using multiple regression partially show that the internal control system has a positivef and significant effect on the quality of local government financial reports. The human resource competency has a positive and insignificant effect on the quality of local government financial reports. The information technology has a positive and insignificant effect on the quality of local government financial reports. The regional financial accounting system has a positive and significant effect on the quality of local government financial reports. Simultaneously shows that internal control system, human resource competency, utilization of information technology and application of the regional financial accounting system effects the quality of local government financial reports. The result of determination coefficient (R^2) showed that that internal control system, human resource competency, utilization of information technology and application of the regional financial accounting system in explaining the stock return was 70,7% and the rest was explained by other unexamined variable in this research.